Impact of light exposure on thyroid-stimulating hormone results using the Siemens Advia Centaur TSH-3Ultra assay. (September 2017) - Armer, Jane; Giles, Diane; Lancaster, Ian; Brownbill, Kathryn
Background: Thyroid-stimulating hormone (TSH) is used as the first-line test of thyroid function. Siemens Healthcare Diagnostics recommend that Siemens Centaur reagents must be protected from light in the assay information and on reagent packaging. We have compared the effect of light exposure on results using Siemens TSH-3Ultra and follicle-stimulating hormone reagents. The thyroid-stimulating hormone reagent includes fluoroscein thiocyanate whereas the follicle-stimulating hormone reagent does not. Methods: Three levels of quality controls were analysed using SiemensTSH-3Ultra and follicle-stimulating hormone reagent packs that had been kept protected from light or exposed to light at 6-h intervals for 48 h and then at 96 h. Results: Thyroid-stimulating hormone results were significantly lower after exposure of TSH-3Ultra reagent packs to light. Results were >15% lower at all three levels of quality control following 18 h of light exposure and continued to decrease until 96 h. There was no significant difference in follicle-stimulating hormone results whether reagents had been exposed to or protected from light. Conclusions: Thyroid-stimulating hormone results but not follicle-stimulating hormone results are lowered after exposure of reagent packs to light. Laboratories must ensure that TSH-3Ultra reagents are not exposed to light and analyse quality control samples on every reagent pack to check that there has not been light exposure prior to delivery. The labelling on TSH-3Ultra reagent packs should reflect the significant effect of light exposure compared with the follicle-stimulating hormone reagent. We propose that the effect of light exposure on binding of fluoroscein thiocyanate to the solid phase antibody causes the falsely low results.